Pedagogical Evaluation of Digital Technology to Enhance Dental Student Learning - Inquimbert, Camille; Tramini, Paul; Romieu, Olivier; Giraudeau, Nicolas (European Journal of Dentistry, 2019)
Objective A large number of digital tools supporting students have emerged over recent years which are encouraged in tutoring. A study conducted at the University of Montpellier (France) among 3rd, 4th, and 5th year dentistry students aimed primarily to identify the type of pedagogical support the students preferred according to their discipline. The secondary aim was to evaluate the student satisfaction after establishing a new pedagogical support.Materials and Methods A total of 165 questionnaires were completed. The main questions concerned pedagogical use of information technology and multimedia tools, choice of dentistry disciplines most justifying their use, and pedagogical gaps in these disciplines. Next, a program of pedagogical videos was developed for the most corresponding discipline. A satisfaction survey was finally conducted.Results Nearly 95.7% of students found online classes and E-learning via the virtual learning environment useful, with the most requested type being video. Demand was stronger in conservative dentistry and endodontics (27%), prosthetics (19%), and periodontology (18%). The most apprehended disciplines were endodontics in the 3rd year, endodontics and prosthetics in the 4th year, and prosthetics in the 5th year. Regarding satisfaction, 100% of students appreciated these videos and 99.4% considered they fulfilled expectations.Conclusion All students requested videos, especially for clinical subjects such as endodontics. With digital technology, our world is experiencing a technological revolution resulting in many daily life changes. With students evolving in a digitally saturated society, our ways of learning and teaching need rethinking. Digital technology can help improve learning effectiveness and develop pedagogical practices more adapted to today's students.
Keywords: dental students; digital; endodontics; learning; pedagogical